Performance evaluation in MANETs environment - Qabajeh, Mohammad M.; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Qabajeh, Liana K.; Daoud, Jamal Ibrahim (INSI Publications, 2012)
Mobile Ad hoc NETwork (MANETs) are collections of mobile nodes that communicate with each other over wireless links in the absence of any infrastructure or centralized administration. The main characteristics of MANETs are limited bandwidth, limited resources, dynamic mobility, and high contention radio medium. In MANETs, the mobile nodes may be laptops, palmtops, PDAs, mobile phones, or pocket PC with wireless connectivity. Mobility and high cost of these devices makes performance evaluation of this type of environment not easy task. This paper presents the different performance evaluation methods used by the research community. Simulation evaluation method will be discussed in detail since it is considered as one of the most popular evaluation methods. Along with this, a valuable description of the current simulation tools will be provided. In short, this paper provides a road map for researchers in choosing the proper evaluation method and choosing the most a appropriate simulation tool.